Achievements in Mesoporous Bioactive Glasses for Biomedical Applications - María Vallet-Regí; Montserrat Colilla; Isabel Izquierdo-Barba; Chiara Vitale-Brovarone; Sonia Fiorilli (MDPI AG, 2022)
Nowadays, mesoporous bioactive glasses (MBGs) are envisaged as promising candidates in the field of bioceramics for bone tissue regeneration. This is ascribed to their singular chemical composition, structural and textural properties and easy-to-functionalize surface, giving rise to accelerated bioactive responses and capacity for local drug delivery. Since their discovery at the beginning of the 21st century, pioneering research efforts focused on the design and fabrication of MBGs with optimal compositional, textural and structural properties to elicit superior bioactive behavior. The current trends conceive MBGs as multitherapy systems for the treatment of bone-related pathologies, emphasizing the need of fine-tuning surface functionalization. Herein, we focus on the recent developments in MBGs for biomedical applications. First, the role of MBGs in the design and fabrication of three-dimensional scaffolds that fulfil the highly demanding requirements for bone tissue engineering is outlined. The different approaches for developing multifunctional MBGs are overviewed, including the incorporation of therapeutic ions in the glass composition and the surface functionalization with zwitterionic moieties to prevent bacterial adhesion. The bourgeoning scientific literature on MBGs as local delivery systems of diverse therapeutic cargoes (osteogenic/antiosteoporotic, angiogenic, antibacterial, anti-inflammatory and antitumor agents) is addressed. Finally, the current challenges and future directions for the clinical translation of MBGs are discussed.